Toward Perceptive Soft Robots: Progress and Challenges. Issue 9 (13th July 2018) - Wang, Hongbo; Totaro, Massimo; Beccai, Lucia
Abstract: In the past few years, soft robotics has rapidly become an emerging research topic, opening new possibilities for addressing real‐world tasks. Perception can enable robots to effectively explore the unknown world, and interact safely with humans and the environment. Among all extero‐ and proprioception modalities, the detection of mechanical cues is vital, as with living beings. A variety of soft sensing technologies are available today, but there is still a gap to effectively utilize them in soft robots for practical applications. Here, the developments in soft robots with mechanical sensing are summarized to provide a comprehensive understanding of the state of the art in this field. Promising sensing technologies for mechanically perceptive soft robots are described, categorized, and their pros and cons are discussed. Strategies for designing soft sensors and criteria to evaluate their performance are outlined from the perspective of soft robotic applications. Challenges and trends in developing multimodal sensors, stretchable conductive materials and electronic interfaces, modeling techniques, and data interpretation for soft robotic sensing are highlighted. The knowledge gap and promising solutions toward perceptive soft robots are discussed and analyzed to provide a perspective in this field. Abstract : Proprioception and tactile sensing in soft robots are needed for real‐world applications. Various soft sensing technologies that hold promise for inventing sensorized soft robots are available today. However, innovations in robust and high‐performance multimodal sensors, stretchable conductors for electrodes and interconnections, fully integrated and/or wireless electronic interfaces, modeling, and data interpretation methods are highly demanded.